Desain Pengembangan Kurikulum PAI di Masa Pandemi Covid Perspektif Pendidikan Nilai di SMAN 1 Kediri - Maqnunah, Lu'luil; Utomo, Tri Prasetyo (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
In the era of the Covid-19 pandemic that hit the world in 2020, the face-to-face learning process could not be carried out by all educational institutions in Indonesia. However, the education process must continue to ensure that every Indonesian citizen gets an education. This requires all educational institutions to carry out online learning. Moral values ​​also declined due to industrial developments. To be able to improve the decline in these values, one of them is by instilling Islamic religious values ​​in students which are contained in the curriculum. This study tries to reveal how the concept of developing the PAI curriculum at SMAN 1 Kediri during the Covid-19 pandemic took place because it was the oldest school in Kediri and was a favorite school that provided many school programs. This research is a qualitative research with a case study design, data collection through participant observation, in-depth interviews and a plot that includes data reduction, data display, and drawing conclusions. The results of this study are: 1) the concept of curriculum development with situation analysis, selection of objectives, selection of content and materials, selection of methods including online and home visits, summative and formative evaluations. 2) implementation of value education perspective curriculum development using religious values, religious activities, literacy of religious scientific journals, and coaching Islamic dress ethics Keywords: Curriculum Development Design, Values ​​Education